Evaluation of radiological pattern of HSG in female patients with infertility in Katsina Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Hysterosalpingography (HSG), is the radiographic evaluation of the uterine cavity and fallopian tubes after the administration of a contrast medium through the cervical canal.Aims:To determine the pattern of infertility, the risk factors for infertility in women presenting for HSG, and the findings among women with infertility at Federal Medical Centre Katsina.Study Design:Cross-sectional, descriptive study design.Materials and Methods:This was a retrospective study of HSG findings done at the federal medical center Katsina over a 12-month period. Information on the patients was obtained from the Picture Archiving Communication System (PACS) system which includes the presenting clinical history, the age, and the outcome of HSG.Statistical Analysis:Data analysis was performed using SPSS version 23.0.Results:A total of one hundred and forty-four (144) women were examined. Their age ranged from 17 48 years with a mean of 31.2 ± 6.3 years. The most common indication for the procedure was infertility, accounting for 89.6% of all cases. The most common Radiological finding was tubal occlusion (factor), which was seen in 40 patients constituting 28% of the radiological findings. The right tubal occlusion was seen at 11.8% while the left tubal occlusion was seen at 6.9%. Bilateral tubal occlusion was seen in 9.0%.Conclusions:The frequent indication for HSG is infertility and the common finding on HSG was a tubal factor with hydrosalpinx being the frequent cause of infertility in our environment. The right tubal occlusion constitutes a higher percentage than the left. Secondary infertility was more common than primary infertility